The perverse gaze of sympathy sadomasochistic sentiments from Clarissa to Rescue 911 - Hinton, Laura (SUNY series in feminist criticism and theory, 1999)
"Suggesting that sentimental novels, films, and TV melodramas are guided by an ambivalent and sadoerotic sympathy, this book shows sympathetic sentiments to be cultural formulations of male desire, and sympathy itself to be the embodiment of a controlling gaze. In a playful but historically persuasive linkage of diverse texts, Laura Hinton shows how sympathetic spectators love their victims and, in the process, maintain authoritarian codes of sexual and racial difference." -- Jacket.